2019
DOI: 10.3390/ijerph16091646
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Participatory Research and Drug Utilization Research to Improve Childhood Diarrhea Case Management in Ujjain, India: A Cross-Sectional Survey

Abstract: Childhood diarrhea continues to be a major cause of under-five (U-5) mortality globally and in India. In this study, 1571 U-5 children residing in nine rural villages and four urban slums in Ujjain, India were included with the objective to use community participation and drug utilization research to improve diarrheal case management. The mean age was 2.08 years, with 297 (19%), children living in high diarrheal index households. Most mothers (70%) considered stale food, teething (62%), and hot weather (55%) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One explanation for the ignorance regarding the use of ORS or zinc as treatment options for diarrhea among students in the present study may be the lack of knowledge regarding these treatments in resource-poor settings [22]. Studies conducted in resource-poor countries have demonstrated that although communities and healthcare providers in these regions are aware of ORS or zinc, the utilization rates of these treatments are low at both the community and prescriber levels [8,23,24]. Additionally, knowledge of students on breastfeeding was satisfactory before intervention and improved signi cantly after intervention.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…One explanation for the ignorance regarding the use of ORS or zinc as treatment options for diarrhea among students in the present study may be the lack of knowledge regarding these treatments in resource-poor settings [22]. Studies conducted in resource-poor countries have demonstrated that although communities and healthcare providers in these regions are aware of ORS or zinc, the utilization rates of these treatments are low at both the community and prescriber levels [8,23,24]. Additionally, knowledge of students on breastfeeding was satisfactory before intervention and improved signi cantly after intervention.…”
Section: Discussionmentioning
confidence: 71%
“…In India, the number of childhood diarrheal deaths is the highest, with over 400,000 cases recorded annually [8]. Diarrheal deaths are more pervasive in rural areas [9].…”
Section: Introductionmentioning
confidence: 99%
“…Low knowledge on ORT preparation also inhibited its uptake and scale-up [ 33 , 38 ], as incorrect preparation of ORT, which renders the rehydration solution ineffective, lead to misconceptions of the effectiveness of ORT [ 33 ]. Two out of the 6 studies that cited inadequate knowledge were published between 2000 and 2019 [ 34 , 37 ], whilst the remaining 4 were published prior to the year 2000. This suggests that low knowledge and understanding of ORT, although still an obstacle, may not be as relevant of a barrier in the context of implementation, nor as pressing to address when compared to the other more recently studied barriers listed in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge and beliefs about the intervention (characteristics of individuals). Low knowledge and understanding of ORT was largely cited as a barrier to implementation, found in 14 studies [28,[33][34][35][36][37][38][39][40][41][42][43][44][45]. In 6 of these 14 studies, low knowledge of ORT amongst users was a barrier [28,[33][34][35][36][37].…”
Section: Plos Onementioning
confidence: 99%
“…The population having household sanitation system has less chances of developing diarrheal diseases, another source of diarrhea in children <5 years is left over food or spoiled food (Mathur et al, 2019). He also mentioned that other major cause of diarrhea in children is bottle-feeding rather than breastfeeding which increase the risk of diarrhea in children (Suliman, 2017).…”
Section: The Main Causes Of Diarrhea; Infectionmentioning
confidence: 99%